Subject: Motivation can be suppressed, but scientific ability cannot and should not be ignored - Saki, Najmaldin; Haybar, Habib; Aghaei, Mojtaba (Journal of translational medicine, 2023)
According to the faculty bestowed to researchers by God and the task assigned to them, they work to better understand and help improve the level of health, treatment and medical education. [...]cultural, ethnic, racial and political differences and other current conflicts should not be a factor repelling and suppressing medical science research and even slowing down its course. [...]it is imperative that society supports the valuable contributions of all medical researchers to ensure the well-being of individuals and the advancement of health care in general. [...]we need to create a mentoring system where experienced researchers can guide and support young scientists in their work.